Vampire knight. Vol. 18 - Hino, Matsuri (Shojo beat manga., 2013)
"Yukio and Zero team up to go after Kaname. Yuki and Kaname fight each other in the headquarters of the Hunter Society while Sara tries to control Zero through her blood. The female progenitor's origin metal intervenes, and Yuki realizes there is only one way to stop Kaname..."--P. [4] of cover.